Perencanaan Dan Analisa Sudu-Sudu Terhadap Daya Turbin Angin Horizontal Type Multiblade - Syawaluddin, Syawaluddin; Kadir, Kadir; Salimin, Salimin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
The purpose of the study was to design and analyze the influence of the number of Sudu on power and the resulting rounds of turbines. This research is done byexperimental methods of designing, making prototypes and testing. The models of wind turbines used are horizontal shaft wind turbines with a diameter of 30 cm with a number of 3, 4, 5, 6 Sudu. Variations in wind speed were given 3 m/s, 3.8 m/s and 4.6 m/s. The results showed that the highest value of 3.08% in the 6-Sudu wind turbinewith a wind speed given 4.6 m/s, whereas for the lowest value obtained 1.45% in a 3 sudu wind turbine with the given speed of wind 3 m/s. For a tip-speed value of λ =3.19 at wind speed of 4.6 m/s with a 6-Sudu turbine amount, while the lowest value of λ = 0.95 at wind speed of 3 m/s with a total of 3-Sudu turbine. Keywords: Design, turbine, ratio, sudu and power